A Case of Sarcoidosis Disseminated to Skeletal Tissues - Edon Rabinowitz; Chinwe Ogedegbe; Joseph Feldman (University Library System, University of Pittsburgh, 2013)
Sarcoidosis is a systemic granulomatous disease of unknown etiology that typically affects young adults. Diagnostic criteria for sarcoidosis include involvement of two or more of the following organ systems: 1) pulmonary infiltrates; 2) bilateral hilar adenopathy; and 3) skin and/or eye lesions. Musculoskeletal system is less commonly involved. For that reason potential presenting symptoms can vary and make the diagnosis very challenging; particularly if a patient has symptoms that mimic other conditions. Musculoskeletal involvement for example can mimic malignancy. The following case describes a patient with known history of primary metastatic mediastinal Germ Cell Tumor (GCT) with teratomatous elements who is diagnosed with sarcoidosis involving skeletal tissues.